Remote sensing of aerosols, clouds, and precipitation - Islam, Tanvir; Kokhanovsky, Alex A.; Hu, Yongxiang; Wang, Jun 1974 June 15- (Amsterdam Elsevier, 2018)
Remote Sensing of Aerosols, Clouds, and Precipitation compiles recent advances in aerosol, cloud, and precipitation remote sensing from new satellite observations. The book examines a wide range of measurements from microwave (both active and passive), visible, and infrared portions of the spectrum. Contributors are experts conducting state-of-the-art research in atmospheric remote sensing using space, airborne, and ground-based datasets, focusing on supporting earth observation satellite missions for aerosol, cloud, and precipitation studies. A handy reference for scientists working in remote sensing, earth science, electromagnetics, climate physics, and space engineering. Valuable for operational forecasters, meteorologists, geospatial experts, modelers, and policymakers alike.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Atmospheric physics -- Remote sensing; Atmospheric aerosols -- Remote sensing; Clouds -- Remote sensing; Precipitation (Meteorology) -- Remote sensing; Electronic books